Cold‐stored whole blood and platelet counts in severe acute injury: A comparison of four retrospective cohorts. Issue 12 (11th October 2021) - Asif, Maryam; Hasan, Rida A.; Liu, Zhinan; Stansbury, Lynn G.; Hess, John R.
Abstract: Background: Low‐titer group O whole blood (LTOWB) is attractive for acute trauma care as it delivers concentrated and balanced hemostatic resuscitation in single large bags. Whether cold‐stored LTOWB can sustain platelet counts is unclear. Study Design and Methods: Four cohorts of trauma patients—three historic, one retrospective—were identified by their urgency of blood use. Admission and all subsequent platelet counts over the first 24 h of care were compared with t ‐tests. The cohorts were as follows: 1292 patients at Maryland Shock Trauma as described by Stansbury and colleagues in 2013; 35 patients enrolled locally in the 1:1:2 arm of the pragmatic randomized optimal plasma and platelet ratios (PROPPR) trial; 34 patients enrolled locally in the 1:1:1 arm of PROPPR; and 59 patients receiving more than 3 units of LTOWB enroute to or at our Level 1 trauma center, 2019–2020. Results: Mean age of LTOWB units transfused was 9 ± 5 days and mean dose was 5 ± 2 units. All four cohorts were profoundly injured (mean Injury Severity Score ≥ 31), with mean first platelet counts 204–228 K/μ and subsequent counts approximately 100 k/μl lower. Through the first 24 h of care, mean platelet counts decreased least, 79 and 83 10 3 /μl, in the 1:1:1 PROPPR and LTOWB cohorts. Mean platelet counts in patients transfused with LTOWB remained stable after the third hour of care. Discussion: LTOWB transfusion was associated with lesser mean decrease in platelet counts during the first 24 h after injury, similar to those observed among patients receiving components 1:1:1 component in the PROPPR study.